Implementation of Finite State Automata on Pizza Vending Machine System - Muhammad Fathir Aulia; Diky Suryandi; Jesron Nainggolan (CV. Multimedia Teknologi Kreatif, 2025)
This study aims to implement Finite State Automata (FSA) on a pizza machine. FSA is a theoretical computational model used to describe the behavior of a system that can change discretely from one state to another. A pizza machine is a machine used to make pizza automatically. In this study, we design and implement FSA on a pizza machine to regulate the pizza making process. FSA consists of a number of states and transitions between those states. Each state represents a certain stage in the pizza making process, such as adding ingredients, mixing dough, and baking. The programming language and algorithm used are appropriate for implementing FSA on a pizza machine. When the machine is turned on, it will start in the initial state. Then, based on the input given, the machine will switch between different states according to the specified transition rules. By implementing FSA, this study successfully automated the pizza making process on the machine. This reduces dependence on human intervention and increases production efficiency. By using FSA, the pizza machine can operate automatically and produce pizza with high accuracy and efficiency. This study contributes to the development of automation in the food industry and improves the understanding of how to apply FSA in the context of real-world applications. In this study, FSA is used to control a muffin machine, but the FSA concept can also be used in various other automation applications.